Crosssover-first different evolution: a comprehensive post- Hoc analysis - Jason Teo (2017)
Explore a new evolutionary optimization approach using Crossover-First Differential Evolution. Implementation details explained clearly with a comprehensive post-hoc statistical analysis to support the algorithm. Sample code is also provided for a quick implementation.